Self-efficacy’s role within learning a new language during formal education: Systematic review, critical evaluation of past research and paths forward for research and practice - Luke K. Fryer; Chunqi Li; Zhixing Guo; Lishi Liang; Yuchun Zhong (Studies in Second Language Learning and Teaching, 2025)
Self-efficacy is essential for persistence in learning across formal education. There are few subjects in formal education that demand more persistence than learning a new language. Researchers have noted this intersection, resulting in a burgeoning body of research examining self-efficacy’s role within foreign/second (L2) classroom language learning. The present systematic review of this literature (2006-2023) was undertaken to map the journey that the field of L2 formal education-related self-efficacy research has taken. Three research questions were addressed, each seeking to assess the state of this field and open up new avenues for research. To this end, PRISMA guidelines were followed and SSCI was exclusively employed to set a firm lower end on the quality of research reviewed. A search string was carefully designed and the search period was set between 2006 and 2023, beginning with Mills et al. (2006) which is the wellspring through which much of the research in this area has flowed. The 166 articles reviewed suggest a dependence on relatively weak research design (cross-sectional and exclusively self-report) and a predominance of tertiary education (convenience) sampling. We suggest that a lack of integration and/or comparison with longstanding second language acquisition (SLA) theories prevents substantive headway to be made. There is some hope that the dramatic rise in the number of articles has been paired with better research designs and broad array of theories employed. Researchers within and outside SLA will find the gaps presented by this review a useful guide for developing the field going forward.